Hepatitis C - From Infection to Cure 2018
DOI: 10.5772/intechopen.75916
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus and Inflammation

Abstract: Inflammation is often a rapid coordinated response generated in the host against evading microbial infections or tissue injury. Microorganisms like bacteria and viruses instigate inflammation mediated by pro-inflammatory cytokines and activate cascade of signaling events leading to the recruitment of inflammatory cells (neutrophils and macrophages). Although the main function of inflammation is the resolution of infection, several viruses, including the hepatitis C viruses (HCV) have evolved to utilize this ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 149 publications
(156 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that several viruses, as they are hepatitis viruses (hepatitis B virus, HCV) [9,115], respiratory tropism viruses (influenza A virus, respiratory syncytial virus) [116][117][118], deoxyribonucleic acid (DNA) viruses (herpes viruses, such as Herpes simplex virus 1; varicella-zoster virus) [119,120], Vaccinia virus [121], human papillomavirus [122], have an important role in activation the inflammasomes, launching the aforementioned signaling cascade [123].…”
Section: Inflammasomesmentioning
confidence: 99%
“…Studies have shown that several viruses, as they are hepatitis viruses (hepatitis B virus, HCV) [9,115], respiratory tropism viruses (influenza A virus, respiratory syncytial virus) [116][117][118], deoxyribonucleic acid (DNA) viruses (herpes viruses, such as Herpes simplex virus 1; varicella-zoster virus) [119,120], Vaccinia virus [121], human papillomavirus [122], have an important role in activation the inflammasomes, launching the aforementioned signaling cascade [123].…”
Section: Inflammasomesmentioning
confidence: 99%